2007
DOI: 10.1007/s10549-007-9718-1
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and significance of caveolin 2 expression in normal breast and invasive breast cancer: an immunofluorescence and immunohistochemical analysis

Abstract: Our results demonstrate that CAV2 is preferentially expressed in basal-like cancers and is associated with poor prognosis. Further in vitro studies are required to determine whether CAV2 has oncogenic properties or is only a surrogate marker of basal-like carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
48
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(54 citation statements)
references
References 53 publications
5
48
1
Order By: Relevance
“…Furthermore Savage et al, have recently reported high prevalence of CAV1 and CAV2 expression in basal-like breast carcinomas (Savage et al, , 2008, and observed CAV1 gene amplification in a small subgroup of basal-like breast cancers (Savage et al, , 2008. Moreover, these findings support Pinilla et al who described an association between CAV1 expression and sporadic basal-like breast cancers and familial BRCA1 tumours (Pinilla et al, 2006).…”
supporting
confidence: 52%
See 2 more Smart Citations
“…Furthermore Savage et al, have recently reported high prevalence of CAV1 and CAV2 expression in basal-like breast carcinomas (Savage et al, , 2008, and observed CAV1 gene amplification in a small subgroup of basal-like breast cancers (Savage et al, , 2008. Moreover, these findings support Pinilla et al who described an association between CAV1 expression and sporadic basal-like breast cancers and familial BRCA1 tumours (Pinilla et al, 2006).…”
supporting
confidence: 52%
“…Despite the controversy about the distribution of CAV1 and CAV2 in normal and invasive breast cancer (Yang et al, 1998;Hurlstone et al, 1999;Chen et al, 2004;Sagara et al, 2004;Park et al, 2005; Van den Eynden et al, 2006), recent studies confirmed the preferential expression of both genes and their proteins in normal myoepithelial cells (Pinilla et al, 2006;Savage et al, 2007Savage et al, , 2008. Furthermore Savage et al, have recently reported high prevalence of CAV1 and CAV2 expression in basal-like breast carcinomas (Savage et al, , 2008, and observed CAV1 gene amplification in a small subgroup of basal-like breast cancers (Savage et al, , 2008.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 More recently, a subgroup of lobular carcinomas has been shown to express high-molecular-weight cytokeratins, 41 however it remains to be determined whether these cases truly show a basal-like transcriptome. The majority of basal-like breast cancers lack or show low levels of ER and PR, lack HER2 protein overexpression and HER2 gene amplification, whereas they express genes and proteins usually found in 'basal'/myoepithelial cells of the normal breast including high-molecular-weight cytokeratins (5/6, 14 and 17), 17,19,21,42 P-cadherin, 43 caveolins 1 and 2, 44,45 nestin, 46 aB crystallin, 47,48 CD109, 49,50 and EGFR 17 and, in a minority of cases, harbor EGFR gene amplification 51 or aneusomy. 52 p53 immunohistochemical expression or TP53 gene mutations is observed in up to 85% of cases, 53,54 and alterations of the pRB and p16 G1/S cell-cycle checkpoint are remarkably prevalent in these cancers.…”
Section: What Is a Basal-like Breast Cancer?mentioning
confidence: 99%
“…The expression profile of luminal cells is dominated by ESR1 (ERa) expression and that of a large number of genes that are associated with oestrogen response in breast cancer including FOXA1, TFF1, AGR2 and GATA3 [19]. Basal specific genes in breast cancer cell lines included two isoforms of caveolin (CAV1 and CAV2), as well as VIM, LY6K and PRNP as previously described [28][29][30]. These genes correlate well with our previous reports of oestrogen responsive genes in primary breast cancers [19] and with genes associated with the basal-like phenotype of breast epithelial cells [26] and primary basal-like breast cancers [3].…”
Section: Unsupervised Clustering Analysis Of Gene Expressionmentioning
confidence: 99%